(untitled) (Ozone Therapy Global Journal, 2018)
Ulcers of the lower limb are a frequent and multifactorial condition with poor remission and high recurrence rates despite the implementation of multimodal management. That is why complementary therapies to the surgical and wound clinic management constitutes nowadays an option with satisfactory outcomes. The vasodilator, antioxidant, fibrinolytic, healing, oxygenating and antimicrobial effects makes ozone a high impact medicine that must be administrated by specialized physicians. In this article, successful outcomes in the management of these lesions with ozone are illustrated, a therapy described since the last century and still not popularized in our environment. Similarly, some cases are presented, the literature is reviewed and the management guidelines that allow and support its use safely are given